Superparamagnetic Iron Oxide Sentinel Node Tracer Injection: Effects on Breast MRI Quality. Issue 6 (27th October 2020) - Chapman, Molly C; Lee, Amie Y; Hayward, Jessica H; Joe, Bonnie N; Price, Elissa R
Abstract: Objective: To evaluate the MRI artifact rendered by the typical injection of a ferromagnetic tracer now being intermittently used for intraoperative sentinel node (SN) identification at our institution, and to explore its impact on postoperative imaging and management. Methods: This study was Institutional Review Board-approved and granted a waiver of consent. A database search tool was used to identify MRI exams performed on patients who had previously undergone breast-conserving surgery with use of a superparamagnetic iron oxide (SPIO) SN tracer between January 1, 2015, and May 1, 2020. MRI reports, images, and relevant demographic, oncologic, and surgical history were collected. The presence or absence of SPIO residue on breast MRI, as well as its impact on image quality, were extracted from the prospective reports. Results: A total of 21 MRI exams were identified in 16 patients who had undergone breast-conservation therapy for cancer with use of SPIO SN tracer. Mean time from particle injection to baseline postoperative MRI exam was 10.8 months. All reports (21/21) noted evidence of SPIO residue. Of these, 5/21 were assessed as non-diagnostic; the remainder were assessed as limited. Conclusion: Radiologists should be aware of the use of superparamagnetic tracers for SN identification and the impact on the quality of future MRI examinations. Alternative injection approaches are being developed and sequence parameters adjusted to minimize artifact.